Political economy of road maintenance: a utility diagnostic. Issue 1 (2nd January 2019) - Streatfeild, Jeremy
ABSTRACT: Sub-Saharan Africa requires US30 billion annually for its infrastructure maintenance, with every dollar spent saving the economy about four times that. However, many governments still do not recognise the need for road maintenance, increasing vehicle operating costs – to more than 1% of GDP in some regions. Still, there are too few political economy diagnostics of this problem and policy responses aiming to ring-fence dedicated funds have had mixed results. This article proposes a diagnostic through which to understand the institutional root causes of the problem using the case of Moldova.